Therapeutic Efficacy of Artificial Intelligence based Counselling for Anxiety and Depression: A Systematic Review - Tanya Kaushik; Smriti Sethi (Recent Trends in Social Studies, 2025)
Background: The occurrence of the COVID-19 pandemic resulted in a notable rise in the prevalence of mental health issues, majorly anxiety and depression. Treatments like cognitive behavioural therapy (CBT) conducted in a face-to-face setting, have consistently demonstrated their effectiveness. Though not always accessible or reasonably priced for everyone, face-to- face treatment environments offer great assistance. AI-based counselling is starting to be a good replacement for those in need of real-time, tailored mental health assistance via virtual experts and conveniently available chatbots. Objective: The aim of this article is to evaluate the effectiveness and development of AI-based counselling in the treatment of anxiety and depression. This paper understands the effects of AI-driven interventions with respect to traditional face-to-face therapy. Main concentration being on the evaluation of user engagement, treatment adherence, and the overall effect on mental health outcomes. Methodology: A comprehensive review of 40 research papers published between 2012 and 2024 was used. This paper investigated the efficacy of AI-powered therapy in the treatment of anxiety and depression. The research was chosen based on specific criteria that prioritised AI-driven remedies and compared them to conventional therapies in terms of user satisfaction, results, and engagement. Conclusion: Including artificial intelligence into therapy has enormous opportunity to increase the accessibility and customisation of mental health treatments to satisfy specific demands. Studies reveal that merging artificial intelligence methods with conventional therapy can significantly help to reduce anxiety and sadness. Combining artificial intelligence techniques with traditional therapy may greatly improve the control of anxiety and depression. Still, challenges remain maintaining the essential human connection, motivating consumers, and facing moral conundrums. Further research is necessary to improve these instruments and easily include them with conventional therapy, ensuring their effectiveness and availability for a population seeking mental health help.
Keywords: AI counselling; Anxiety; Depression; psychotherapy; treatment adherence